2018
DOI: 10.1093/jme/tjy123
|View full text |Cite
|
Sign up to set email alerts
|

Faunistic Analysis of the Families Calliphoridae and Mesembrinellidae (Diptera) at Jardim Botânico do Rio de Janeiro, Brazil

Abstract: Flies of the family Calliphoridae play a variety of ecological roles. They carry various pathogens and cause myiasis in humans and livestock, but they are useful to forensic entomology and in larval therapy. Mesembrinellidae flies, formerly classified in the family Calliphoridae, are good bioindicators of human interference in natural environments. In this study, we carried out an inventory of the Calliphoridae and Mesembrinellidae at four collecting sites within the Jardim Botânico do Rio de Janeiro. Eight tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
3
0
2
Order By: Relevance
“…Because these organisms can be found in natural and/or urban environments [29], it is important to study the faunal aspects within a biome, space, and time. In work carried out at the Botanical Garden of Rio de Janeiro, [30] found greater diversity of Calliphoridae species in less anthropic areas. In this study, the Shannon-Wiener-Wiener diversity index, which states that the higher the value of this index, the greater the uncertainty that a species belongs to the individuals selected in the sample, also varied in the environments throughout the seasons, ranging from 1.49 to 2.22 in the forest environment; 0.66 to 1.83 in the rural environment; and 0.69 to 1.92 in the urban environment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because these organisms can be found in natural and/or urban environments [29], it is important to study the faunal aspects within a biome, space, and time. In work carried out at the Botanical Garden of Rio de Janeiro, [30] found greater diversity of Calliphoridae species in less anthropic areas. In this study, the Shannon-Wiener-Wiener diversity index, which states that the higher the value of this index, the greater the uncertainty that a species belongs to the individuals selected in the sample, also varied in the environments throughout the seasons, ranging from 1.49 to 2.22 in the forest environment; 0.66 to 1.83 in the rural environment; and 0.69 to 1.92 in the urban environment.…”
Section: Discussionmentioning
confidence: 97%
“…macellaria was constant and intermediate in the rural environment and accessory and constant in general. Unlike [30], who considered it as intermediate and accidental, however, the frequency of this species only in rural areas is due to the ecological displacement caused by competition with the exotic species of the genus Chrysomya that have become dominant in urban areas [42]. Representatives of the genera Hemilucilia and Paralucilia are, respectively, partially and substantially predominant in preserved areas [40,43], whereas in the present study, H. segmentaria and H. semidiaphana were common in urban and rural environments; in addition, in this study, it was demonstrated that Mesembrinellidae prefers putrefied bait, and H. benoisti and P. nigrofacialis also appeared in greater abundance in this type of bait.…”
Section: Discussionmentioning
confidence: 99%
“…É caracterizada como necrófaga, pelo hábito das larvas alimentarem-se de matéria animal em decomposição Linhares 2007); por isso tem se destacado em estudos feitos em muitas localidades em todo o Brasil. É registrada quase exclusivamente em áreas de floresta (Ferraz et al, 2010; Zuben 2012) e quando em área urbana, ocorre principalmente em fragmentos de floresta (Figueiredo et al, 2018).…”
Section: Hemiluciliaunclassified
“…To avoid possible edge effects, all the samples were installed with a minimum distance of 300 meters from the forest edge. From this limit, four trails with a minimum In each trail, five trees were systematically selected, with distances of 200m between them, to reduce the autocorrelation effect and ensure sample independence (Figueiredo et al 2018, Dufek et al 2020. None of the selected trees were fruit trees or were in bloom, thus avoiding interferences from other fly attractants (Figure 1-2a).…”
Section: Sample Designmentioning
confidence: 99%